2021
DOI: 10.3390/sym13091681
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of the Thermodynamic Characteristics and Physicochemical Properties of Symmetric and Asymmetric Isomeric Compounds for Identification in Chromatography-Mass Spectrometry

Abstract: A combination of theoretical and experimental approaches was applied to determine the chromatographic rules of isomeric compounds’ behavior for preliminary identification. In gas chromatography-mass spectrometry (GC-MS), identification is performed by spectra matching, however, difficulties arise with isomeric compounds, which cannot be distinguished from each other without additional information. The thermodynamic characteristics of the adsorption of symmetric and asymmetric isomers of сhlorophenylphenols, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The pairs of enantiomers could not be discriminated using this technique because they have identical profiles. Given these aspects and the good results that have been presented in similar studies [11][12][13][14][15][16][17], it is expected that the correlation of the profiles with the mass spectra of the chemical standards is only maximum for the truly positive results. Optimizing the experimental impact energy and the correlation relationship could also improve the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pairs of enantiomers could not be discriminated using this technique because they have identical profiles. Given these aspects and the good results that have been presented in similar studies [11][12][13][14][15][16][17], it is expected that the correlation of the profiles with the mass spectra of the chemical standards is only maximum for the truly positive results. Optimizing the experimental impact energy and the correlation relationship could also improve the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally designed as a separation method, chromatography was later perfected to become a formidable analytical method using chemical standards. Recent studies have shown that the qualitative analysis of some symmetric and asymmetric isomers can also be performed by establishing the elution order, based on the thermodynamic characteristics of adsorption, using molecular statistical calculations [12]. Some techniques that use the quantitative structure-fragmentation relationship (QSFR) can filter the candidate structures using the reverse ordering of the calculated formation enthalpies (∆ f H) of their primary ions, together with the corresponding experimental ionic currents obtained by mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of chromatography with mass spectrometry has offered the possibility of analyzing complex mixtures of analytes [5]. In addition to the classical use of standards, they use new variants of data processing and interpretation, which have been effectively translated to computational molecular simulation approaches [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fulfillment of each of these objectives has an original conception and/or route. The optimization of the technique was achieved by group validation of analytes, a variant frequently used in chromatography because it can simultaneously cover a variety of structures [6,8]. The optimization used four independent variables: the quantum chemical (QC) method, the descriptor of calculated energy, the impact energy (IE) of electrons, and the descriptor of experimental energy.…”
Section: Introductionmentioning
confidence: 99%